Adult Student Considerations Regarding a Learning Environment Conditions - Gusho, Leticja Papa (Richtmann Publishing, 2012)
In our society, in our environment and right in front of us are occurring different social, cultural and economical movements,which, considered from professional and scientific point of view, impose a real commitment. In these conditions adults are facing a lot ofchallenges and they return to school to confront these challenges. They want to learn and get the best of this process. But what is thelearning environment condition that is created in classrooms, for adult students? What are the physical conditions in which all thelearning activities take place? The main aim of this paper is to present some of the opinions of the adult students in Korça and ElbasanUniversities that are pursuing their part-time studies, regarding learning environment conditions, where their learning activities takeplace. To analyze the data for this paper are used only the quantitative methods. The sample is adult students that are frequenting parttime study in Korça and Elbasan University. To select the sample from the whole population is used the stage sampling. For gatheringdata are used interviews. The analysis of data has been carried out according to normal statistical methods. In summary, the adultstudents want to learn, but the level of the learning environment condition, which is created in the classrooms, is under the average level.From adult learners’ reports, they emphasise that the institutions should guarantee better accommodation conditions for teaching andlearning activities. Furthermore, lecturers should use more often techniques and methodology that ensure not only engendering thecognitive competences, but also motivate adult students toward learning.